The Effectiveness of Outdoor Study at the Siak Palace Site in Learning Social Studies to Improve Students' Nationalistic Value - Fadillah, Fanny Suci; Komalasari, Kokom; Wiyanarti, Erlina; Rohani, Rohani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research aims to analyze the effectiveness of outdoor study at the Siak Sri Indrapura Palace site in social studies learning to improve students' nationalistic value. The research method used was quasi-experimental with a nonequivalent pre-test and post-test control group research design. The instruments used in this research were pre-test and post-test questionnaires. The population in this study were all grade 11 students. The population of class XI-1 students as the control class and class XI-3 students as experimental class, descriptive analysis of the students’ characteristics in the beginning and end of the avtivity of both students in control class and experimental class. Data analysis uses prerequisite tests, namely the normality test and homogeneity test, and hypothesis testing uses sample t-tests which are analyzed using SPSS. Based on the results of the pre-test and post-test, it shows that using the outdoor study method in learning social sciences is more effective in improving students’ nationalistic character, and this research also reveals that the experimental class that uses the outdoor study method also has better effect on the results compared to learning using the lecture method and watching videos in class.